Determinants of Catastrophic Health Expenditure in Iran - M Ramezanian; P Bastani; SA Hasani; M Abolhallaje; M Kazemian (Iranian Journal of Public Health, 2013)
Background: This study will provide detailed specification of those variables and determinants of unpredictable health expenditure in Iran, and the requirements to reduce extensive effects of the factors affecting households’ payments for health and other goods and services inappropriately.Method: This study aims to identify measures of fair financing of health services and determinants of fair financing contribution, regarding the required share of households that prevents their catastrophic payments. In this regard, analysis of shares of households’ expenditures on main groups of goods and services in urban and rural areas and in groups of deciles in the statistics from households’ expenditure surveys was applied.Results: The growth of spending in nominal values within the years 2002-2008 was considerably high and the rate for out-of-pocket payments is nearly the same or greater than the rate for total health expenditure. In 2008, urban and rural households in average pay 6.4% and 6.35% of their total expenditure on health services. Finally three categories of determinants of unfair and catastrophic payments by households were recognized in terms of households’ socio-economic status, equality/inequality conditions of the distribution of risk of financing, and economic aspects of health expenditure distribution.Conclusion: While extending the total share of government and prepayment sources of financing health services are considered as the simplest policy for limiting out-of-pocket payments, indicators and policies introduced in this study could also be considered important and useful for the development of health sector and easing access to health services, irrespective of health financing fairness